Crisis evangelism preparing to be salt and light when the world needs us most - Neuenschwandern, Mark, 1949-; Neuenschwandern, Betsy, 1948- (Ventura, CA Regal, 1999)
Includes bibliographical references.
Keywords: Evangelistic work; Crisis management -- religious aspects -- Christianity